Smartphone overdependence and quality of life in college students: Focusing on the mediating effect of social withdrawal - Park, Ji Hwan; Choi, Jeong Min (Frontiers in Public Health, 2022)
This study examines the mediating role of social withdrawal in the relationship between smartphone overdependence and quality of life in college students. These three factors were assessed in 125 college students enrolled at a college in South Jeolla Province, South Korea, from September to November 2019. Data analysis was conducted using SPSS version 27.0, including regression to test the research hypothesis and a Sobel test to assess the significance of the mediation. It was found that social withdrawal completely mediates the relationship between smartphone overdependence and quality of life in college students. Several means of improving the quality of life of college students are identified based on this finding. First, colleges could provide financial support for community programs such as membership training and club activities. Second, an in-college system could be built that enables early intervention in cases of social withdrawal in students. Third, closely linked programs could be designed to provide effective professional counseling to college students experiencing strong social withdrawal. Fourth, college faculty could receive psychoeducation on social withdrawal. Fifth, as various mediating variables may exist in the relationship between smartphone overdependence and quality of life and only social withdrawal was considered in this study, subsequent studies could consider the effects of more diverse psychological and social variables.